Trysting Genres: Andrew Lang’s Fairy Tale Methodologies - Clark Hillard, Molly (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2013)
Andrew Lang represents an alternative model to the cult of the solo literary genius that occupied so much of the Victorian literary landscape, a model that is defined by collaboration and coterie production, and one that troubles the rigidities of discipline and genre. This essay, with Lang at its core, throws into relief the extent to which all authorship is a collective endeavor between forms and across time. While Lang’s entire oeuvre is important, this essay is most interested in his work on the fairy tale. For this essay, Lang is one practitioner of a kind of discourse generated in the wake of the Victorian fairy tale surge—the widespread incorporation of fairy tales into other Victorian literary and cultural forms like theater, fine arts, and literature. What a fairy tale was, and to whom or to what it belonged, were questions that frequently ran through contemporary discourse about literary production, like the copyright debates, the plagiarism debates, and the ongoing discussion about whether social science writing was or was not a kind of creative work. Lang’s treatment of the fairy tale, especially in his popular Colored Fairy Books, places him at the end of this century-long conversation about the nature of originality. This essay considers how Lang’s position at the center of multiple, linked networks might owe something, or everything, to his play with the fairy tale, arguably the most “networked” of forms. Lang’s very interdisciplinarity can help us to understand the extent to which the fairy tale’s language, figures, structure, authors, and methods of production had come to influence other forms of cultural production and consumption.